Dysregulation of Mitochondrial Homeostasis in Cardiovascular Diseases - Ricky Patil; Hui Wang; Matthew Kazaleh; Gorav Ailawadi; Morgan Salmon (Pharmaceuticals)
Mitochondria dysfunction plays a central role in the development of vascular diseases as oxidative stress promotes alterations in mitochondrial morphology and function that contribute to disease progression. Redox imbalances can affect normal cellular processes including mitochondrial biogenesis, electrochemical equilibrium, and the regulation of mitochondrial DNA. In this review, we will discuss these imbalances and, in particular, the potential role of mitochondrial fusion, fission, biogenesis, and mitophagy in the context of vascular diseases and how the dysregulation of normal function might contribute to disease progression. We will also discuss potential implications of targeting mitochondrial regulation as therapeutic targets to treat vascular disease formation.